2014
DOI: 10.2217/nnm.13.25
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Intravenously Administered Transferrin-Conjugated Dendriplexes on Prostate Carcinomas

Abstract: This version is available at https://strathprints.strath.ac.uk/42676/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…In addition, we found that the efficacy could be further improved by targeting the liposomes to tumour cells using transferrin. 41 Liposome-mediated drug delivery avoided the docetaxel-associated toxicities that we previously observed. Future clinical study does not necessarily involve liposomes as both drugs are extensively used clinically, and the relative dosing of the two agents can be tested easily.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, we found that the efficacy could be further improved by targeting the liposomes to tumour cells using transferrin. 41 Liposome-mediated drug delivery avoided the docetaxel-associated toxicities that we previously observed. Future clinical study does not necessarily involve liposomes as both drugs are extensively used clinically, and the relative dosing of the two agents can be tested easily.…”
Section: Discussionmentioning
confidence: 81%
“…The PAMAM-PEG-Angiopep/pORF-TRAIL NPs could penetrate the blood-brain barrier (BBB) and target glial cells based on Angiopep-2-mediated delivery, with hight transfection efficiency. Another strategy has been reported in which transferrin (Tf) was conjugated to a generation 3 diaminobutyric polypropylenimine (DAB) dendrimer; this delivery system harbors plasmids encoding for TNF-α, TRAIL, or IL-12 and leads to therapeutic effects on prostate tumors following intravenous administration [63]. In addition, lactoferrin (Lf)-bearing DAB dendriplexes showed similar efficacy [64].…”
Section: Nonviral Vectorsmentioning
confidence: 99%
“…Antibody anti-CD71-modified PA-MAM dendrimer shows much higher cellular uptake and more efficient antiapoptotic gene silencing in prostate cancer cells compared to no-antibody ones [162]. Transferrin-conjugated dendrimers can highly express tumor necrosis factor α (TNFα) by delivery of plasmids in prostate cancer cells in vitro and in vivo [163]. Major histocompatibility complex (MHC) class II-targeting peptides modified dendrimers can deliver DNA-based vaccines to specifically accumulate in professional antigen-presenting cells, which enhances immunostimulatory potency and provides an immunotherapy for tumor treatment [164].…”
Section: Dendrimer Conjugates In Gene Therapymentioning
confidence: 99%